2014
DOI: 10.1073/pnas.1408409111
|View full text |Cite
|
Sign up to set email alerts
|

The MuSK activator agrin has a separate role essential for postnatal maintenance of neuromuscular synapses

Abstract: The motoneural control of skeletal muscle contraction requires the neuromuscular junction (NMJ), a midmuscle synapse between the motor nerve and myotube. The formation and maintenance of NMJs are orchestrated by the muscle-specific receptor tyrosine kinase (MuSK). Motor neuron-derived agrin activates MuSK via binding to MuSK's coreceptor Lrp4, and genetic defects in agrin underlie a congenital myasthenic syndrome (an NMJ disorder). However, MuSK-dependent postsynaptic differentiation of NMJs occurs in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…MG‐like symptoms were observed in rabbits immunized with LRP4, and, importantly, transfer of anti‐LRP4 IgG from immunized rabbits into naive mice caused similar MG‐like symptoms, reduced CMAP, and impaired transmission in recipients. Together, these observations demonstrate that LRP4 antibodies are causal to MG and support the notion that the agrin signaling is critical for NMJ maintenance in adulthood …”
Section: Anti‐lrp4 and Anti‐agrin Antibodies In Mgsupporting
confidence: 75%
“…MG‐like symptoms were observed in rabbits immunized with LRP4, and, importantly, transfer of anti‐LRP4 IgG from immunized rabbits into naive mice caused similar MG‐like symptoms, reduced CMAP, and impaired transmission in recipients. Together, these observations demonstrate that LRP4 antibodies are causal to MG and support the notion that the agrin signaling is critical for NMJ maintenance in adulthood …”
Section: Anti‐lrp4 and Anti‐agrin Antibodies In Mgsupporting
confidence: 75%
“…Another rather unusual aspect of Dok-7 signaling is the finding that forced overexpression of Dok-7 is sufficient to form AChR clusters in cultured myotubes and to allow mice to survive for several weeks in the absence of agrin (334,422). Similarly, expression of Dok-7 via AAV vectors in skeletal muscles enlarges the NMJ and thereby ameliorates the disease in a mouse model for Emery-Dreifuss muscular dystrophy (11).…”
Section: Molecules Expressed In Musclementioning
confidence: 99%
“…; Tezuka et al . ). To examine whether MuSK‐mediated signaling is affected by postnatal knockdown of dok‐7 expression, we evaluated mRNA levels of several NMJ components that are known to be regulated by MuSK (Jones et al .…”
Section: Resultsmentioning
confidence: 97%
“…However, we previously showed that agrin has an essential role aside from MuSK activation in postnatal NMJ maintenance, but not in embryonic NMJ formation (Tezuka et al . ). In addition, collagen α3‐6 (IV) chains and biglycan selectively participate in the postnatal maintenance of NMJs (Fox et al .…”
Section: Discussionmentioning
confidence: 97%